Rupture - Ragnar Jónasson, 1976- (Ragnar Jónasson, 1976- Dark Iceland series., 2019)
Young policeman Ari Thór tries to solve a 50-year-old murder when new evidence surfaces. But the case proves difficult in a town where no one wants to know the truth, where secrets are a way of life. He's assisted by Ísrún, a news reporter in Reykjavik who is investigating an increasingly chilling case of her own. Things take a sinister turn when a child goes missing in broad daylight. With a stalker on the loose, and the town in quarantine, the past might just come back to haunt them.